The myth of the “populous Earth”: an analysis of the Jewish Exile in the light of recent historical and archaeological research - Neto, Tiago Abdalla Teixeira (Vox Scripturae - Revista Teológica Internacional, 2017)
In the 1990s, the scholar Hans Barstad developed the idea, initially proposed by Robert P. Carroll, of the “Myth of the Empty Land”, in which the conception of an abandoned Jewish territory with much of the people exiled would have been a later creation of a small Jewish community zealous for Zion, who had returned from Babylon. According to this theory, society in Judah continued to function normally with its peasants, artisans, merchants and Temple officials. However, recent studies have challenged this hypothesis and indicated — through archaeological, documentary and demographic evidence — a striking event in the history of Israel that can be identified with the exile and destruction presented in the Hebrew Bible. The purpose of this paper is therefore to analyze these recent findings and researches in a panoramic way and to demonstrate how they illuminate the understanding of what the destruction of Judah and the exile of the people of that land meant in the sixth century B.C.